The Effect of MoS2 and Si3N4 in Surface Plasmon Resonance Biosensors for HIV DNA Hybridization Detection: A Numerical Study - Talia Tene; Diana Coello-Fiallos; María de Lourdes Palacios Robalino; Fabián Londo; Cristian Vacacela Gomez (Micromachines)
This study presents a numerical investigation of surface plasmon resonance (SPR) biosensors incorporating silicon nitride (Si3N4) and molybdenum disulfide (MoS2) for HIV DNA hybridization detection. By optimizing the thickness of Ag and Si3N4 and the number of MoS2 layers, two configurations, Sys2 (Ag-Si3N4) and Sys3 (Ag-Si3N4-MoS2), were selected for comparative analysis. Performance metrics, including the resonance angle shift, sensitivity, detection accuracy, and quality factor, demonstrated that Sys2 achieved the highest sensitivity of 210.9°/RIU and an enhanced figure of merit (86.98 RIU−1), surpassing state-of-the-art SPR sensors. Although Sys3 exhibited a lower sensitivity of 158.1°/RIU due to MoS2-induced optical losses, it provided a lower limit of detection, suggesting a trade-off between sensitivity and spectral broadening. Compared to previous SPR biosensors, the proposed configurations achieve superior sensitivity while maintaining stability and selectivity, positioning them as promising candidates for next-generation nucleic acid detection platforms.